Metastatic testicular carcinoma from the colon with clinical, immunophenotypical, and molecular characterization: Report of a case - TIONG HO YEE (LIPPINCOTT WILLIAMS & WILKINS, 2022)
DISEASES OF THE COLON & RECTUM